Pewarnaan Titik Ketakteraturan Lokal Graf Pensil - Kristiana, Arika Indah; Saputra, Guntari (Universitas Islam Jember, 2024)
The graph used in this paper is a simple and connected graph consisting of a set of vertices and a set of edge . A function is called vertex irregulaarity labelling and . If for every , where and then, f is called local irregularity vertex coloring. The chromatic number of the local irregular vertex coloring of graph is denoted by , which is the minimum cardinality of the largest label of all local irregular vertex coloring. In this article we will learn about coloring points of local irregularities in pencil graphs and finding the exact value of the chromatic number. Keywords: local irregularity; vertex coloring; pencil graphs